"Educational Facials": A Healing Tool for the Beautiful Struggle - Kari Kokka; Michelle Cody (MDPI AG, 2024)
Critical educators of Color often work to support their students to work toward justice. However, because we live and work in a society imbued with white supremacy, cisheteropatriarchy, and additional systems of oppression, students and colleagues may resist efforts toward equity and racial justice, especially in mathematics education with women of Color instructors. In this paper, two mathematics educators, a Japanese American woman and a Black woman, elaborate a theory of educational facials, first coined by the second author in 2015. The theory of educational facials is an analytic tool for healing from and navigating harmful school climates. The authors operationalize the theory of educational facials as a lens to investigate examples from their own experiences negotiating unhealthy environments. The article shares descriptions of types of educational facials (e.g., do-it-yourself empowerment educational facial) and concludes with discussion of systemic change to promote healthy, liberatory, justice-oriented school spaces.